Analysis of the Relationship between NLRP3, Ferritin, MDA, and Catalase Enzyme in Patients with Beta-Thalassemia Major: A Clinical Study - Al-Dhalimi, Ali Abd Al-Bari; Al-Abady, Zainab N. (Journal of Biomedicine and Biochemistry, 2025)
Background :The thalassemia syndromes are a group of inherent hemolytic anemias characterized by the decrease or absence of the synthesis of one or more globin chains of hemoglobin. Elevated levels of NOD-like receptor protein 3 (NLRP3) and ferritin, along with oxidative stress markers such as malondialdehyde (MDA) and catalase activity, have been linked to thalassemia disease progression and prognosis.Aim :This study aims to investigate the relationship between serum levels of NLRP3, ferritin, MDA, and catalase activity in thalassemia patients compared to healthy controls, providing insights into potential diagnostic and prognostic biomarkers.Materials and Methods :Seventy-five patients with beta-thalassemia major aged 6-18 years along with forty-five normal people of the same age without any history of hematological diseases, chronic diseases, acute illness, or infection. Patients who met the selection criteria were included in the study. Serum levels of NLRP3, ferritin, MDA, and catalase were analyzed using enzyme-linked immunosorbent assay (ELISA) and spectrophotometric methods.Results: The study found elevated levels of NLRP3 in thalassemia patients (7.006 ± 1.014) compared to the healthy group (1.35 ± 0.2868), with a P value of 0.0003. Ferritin levels were also higher in patients (1576 ± 85.09) (ng/ml) compared to the healthy group (73.1 ± 13.67) (ng/ml), with a P value of